Genomic landscape and comparative analysis of tissue and liquid-based NGS in Taiwanese anaplastic thyroid carcinoma - Chun-Nan Yeh; Shu-Fu Lin; Chia-Ling Wu; Miaw-Jene Liou; I-Wen Chen; Chiao-Ping Chen; Ching-Fu Chang; Qi‑An Wang; Chiao-En Wu (npj Precision Oncology)
Abstract Anaplastic thyroid carcinoma (ATC) is an aggressive cancer that requirements rapid diagnosis and multimodal treatment. Next-generation sequencing (NGS) aids in personalized therapies and improved trial enrollment. The role of liquid-based NGS in ATC remains unclear. This study analyzed ATC samples using tissue-based NGS, liquid-based NGS, or both platforms. Genetic alterations showed highly heterogeneity, including mutations in RAS/RAF/MEK/ERK, PI3K/AKT/mTOR, cell cycle regulation, other receptor tyrosine kinases, DNA damage response, mismatch repair, and chromatin remodeling. TP53 (65.4%) and BRAF (30.8%) were the most frequently mutated genes in tissue NGS. In paired samples, the concordance rates were 69.2% for TP53 and 84.6% for BRAF. One of two patients treated with dabrafenib and trametinib showed a copy number gain in post-treatment tissue NGS, potentially indicating resistance. Liquid biopsy provides valuable supplementary information when tissue samples are insufficient. Further studies are necessary to understand resistance mechanisms and develop strategies to overcome them in BRAF-targeted therapy.